Sequential bronchoplastic upper lobectomy as a surgical component of multimodal treatment for synchronous bilateral multiple primary non-small cell lung cancer - O. I. Kit; I. N. Turkin; D. A. Kharagezov; Yu. N. Lazutin; I. A. Leiman; A. V. Chubaryan; E. A. Mirzoyan (Сибирский онкологический журнал, 2022)
Relevance. Lung cancer (LC) is the leading cause of cancer-related death worldwide including Russia. Surgery remains the standard of care for early non-small cell lung cancer (NSCLC). However, as the disease progresses, the risk of metastasis increases, and the effectiveness of surgical intervention decreases. The treatment strategy for patients presenting with a single NSCLC has long been developed. However, for patients with two or more tumors, especially in both lungs, the correct choice is determined by many additional factors. Currently, the view on the surgical treatment for synchronous multiple primary NSCLC has changed dramatically. However, patients with locally advanced synchronous NSCLC often receive conservative treatment, and for those who do undergo surgery, the prognostic factors are unclear. The disease prognosis in patients after surgical treatment for bilateral synchronous multiple primary NSCLC has now been proven to be favorable. Pneumonectomy is believed to have no any negative effect on survival; however, several authors reported on a 1.5-2-fold increase in postoperative mortality in a series of surgeries for synchronous NSCLC. Case description. We herein report a case in which extended bronchoplastic upper lobectomy was successfully applied in the treatment of a patient with bilateral synchronous NSCLC. Our experience demonstrates that the sequential application of modern therapeutic modalities results in satisfactory long-term outcomes in the treatment of locally advanced LC.Conclusion. Due to its uniqueness, this clinical case will be useful for developing treatment strategy for synchronous locally advanced NSCLC as well as for improving the quality of life of patients and increasing their survival.